2018
DOI: 10.11137/2018_1_351_364
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Accuracy and Calibration of Digital Elevation Models (DEMs) for the Piranhas-Assu River Basin, Rio Grande do Norte, Brazil

Abstract: ResumoA crescente demanda em uso de dados altimétricos de alta precisão vertical, para o uso em trabalhos ambientais, vem aumentando de forma significativa nos últimos anos. Entretanto, cuidados especiais devem ser tomados para a utilização desse tipo de produto, principalmente na verificação do seu erro vertical. Esse trabalho teve como objetivo avaliar a qualidade vertical e desenvolver uma metodologia de calibração de Modelos Digitais de Elevação (MDEs) obtidos a partir dos levantamentos realizados pela Shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, it was submitted to the calibration process for adjustment to the local reference geodetic system. The DEM calibration is a mandatory pre-processing adoption that provides improvement of both DEM vertical accuracy and linking to the geodetic system (Araújo et al, 2018). This study adopted the SRTM calibration method suggested by Araújo et al (2018).…”
Section: Digital Elevation Model (Dem) Calibrationmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it was submitted to the calibration process for adjustment to the local reference geodetic system. The DEM calibration is a mandatory pre-processing adoption that provides improvement of both DEM vertical accuracy and linking to the geodetic system (Araújo et al, 2018). This study adopted the SRTM calibration method suggested by Araújo et al (2018).…”
Section: Digital Elevation Model (Dem) Calibrationmentioning
confidence: 99%
“…The DEM calibration is a mandatory pre-processing adoption that provides improvement of both DEM vertical accuracy and linking to the geodetic system (Araújo et al, 2018). This study adopted the SRTM calibration method suggested by Araújo et al (2018). These authors used control points of high vertical accuracy linked to the Brazilian Geodetic System (in Portuguese Sistema Geodésico Brasileiro -SGB) for calibrating the DEMs.…”
Section: Digital Elevation Model (Dem) Calibrationmentioning
confidence: 99%
See 3 more Smart Citations